Little Red Riding Hood - Alperin, Mara; Schauer, Loretta (London Little Tiger Press, 2013)
Little Red Riding Hood sets off to bring a basket of fruit to her grandmother. On her way, Little Red meets a wolf. When Little Red arrives at Grandma's house, there's someone hairy and very scary waiting in Grandma's bed! Will Little Red be breakfast for the big, bad wolf? My First Fairy Tales are a magical introduction to the well-loved stories that are a key part of every childhood. With fresh and fun illustrations, this simple re-telling of a classic fairy tales makes a perfect bedtime read for three to six year olds
English stories
1 2 13 23
Keywords: English stories